DETERMINANTS OF THE LEVEL OF COMPLETION FOLLOWING UP RECOMMENDATIONS ON THE AUDIT RESULTS OF BPK RI TO LOCAL GOVERNMENTS - Ken Yulita Maulydina Kusumarini; Novita Weningtyas Respati (SIMAK, 2022)
This study aims to examine and analyze the influence of the factors that influence the level of completion of follow-up recommendations on the results of the examination of the BPK RI in district/city governments on the islands of Sumatera and Kalimantan. The population in this study are all district/city governments located on the islands of Sumatera and Kalimantan. Determination of the research sample using a purposive sampling technique and obtained as many as 564 samples consisting of 128 districts/cities. Multiple linear regression was used as a data analysis technique.The results of this study indicate that the length of office of the regional head affects the level of completion of the follow-up to the recommendations of the BPK RI examination results, while the auditor's proficiency, the type of local government, the number of SKPD, the age of the local government and dependence on the central government do not affect the level of completion of the follow-up to the recommendations of the examination results BPK RI.